VSC-HVDC System Based on Multi-converters and Its Experimental Research - DENG Ming; JING Huabing; HUANG Zhiguo; BI Jinrong; ZHANG Zhuo; HE Bojun (Kongzhi Yu Xinxi Jishu)
It mainly introduced the working principle and converter mathematical model of VSC-HVDC, put forward a novel VSC-HVDC system based on multi-converters, and then analyzed its structure characteristics and control strategies in detail, finally built a set of VSCHVDC experimental system according to the proposed multi-converters topology. The experimental results show that the VSC-HVDC system based on multi-converters has excellent performance such as stable power transfer, high power factor, low harmonic content, good controllability, etc., and has an extensive engineering application prospect.